Over-the-counter naproxen in rheumatology practice: scope and therapeutic benefits - E. S. Filatova; A. E. Karateev (Современная ревматология)
Over-the-counter nonsteroidal anti-inflammatory drugs (NSAIDs) contain a relatively low dose of their active ingredient and are intended for short-term use (for 3–5 days). They are effective and convenient in the treatment of musculoskeletal pain in many clinical situations in rheumatology practice. Over-the-counter naproxen 275 mg has a proven analgesic efficacy, with its action duration of up to 12–15 hours after single-dose administration, and a favorable safety profile. It can be used successfully for the management of exacerbations of osteoarthritis, short-term episodes of pain with a stable course of autoimmune inflammatory rheumatic diseases, with acute nonspecific back pain and at the onset of periarticular soft tissue pathology. With allowance made for the national guidelines for the use of NSAIDs, this drug can be prescribed for a short time as an analgesic therapy in patients at high risk for cardiovascular events. It is of particular value for outpatient practice, since the patients can freely purchase and use it in accordance with the principles of responsible self-medication.